Reasons for Functional Decline Despite Reductions in Knee Pain: The Multicenter Osteoarthritis Study - White, Daniel K. (American Physical Therapy Association, 2011)
BACKGROUND: The majority of interventions for knee osteoarthritis aim to reduce knee pain with the assumption that improvements in function will automatically follow. However, this assumption is not universally true, and a paradoxical decline in function is not uncommon following reduction in knee pain. OBJECTIVE: The purpose of this study was to examine what factors beyond knee pain are important for functional decline among people with reductions in knee pain. DESIGN: This was an observational cohort study. METHODS: The Multicenter Osteoarthritis Study (MOST) is a National Institutes of Health–funded longitudinal study of people who have or are at high risk for knee osteoarthritis. This study included individuals who had a meaningful reduction in pain in either knee over 30 months, defined as a 41% decrease in visual analog scale pain score with an absolute decrease of ≥20/100. Meaningful decline in walking speed was defined as a decrease of 0.1 m/s during a 20-m walk. To examine the association of risk factors with meaningful decline in walking speed, risk ratios were calculated and adjusted for potential confounders. RESULTS: Of the 465 people with a meaningful reduction in knee pain (mean [SD] age=63.3 [7.8] years, 67% female, 82% Caucasian, mean [SD] body mass index=31.3 [6.3] kg/m(2)), 20% had a meaningful decline in walking speed. Adjusting for confounders, participants with new comorbidity and those with widespread pain had 1.8 and 1.7 times the risk of decline compared with their counterparts with no comorbidity or widespread pain (adjusted risk ratio=1.8 [95% confidence interval=1.1–3.0] and 1.7 [95% confidence interval=1.1–2.8], respectively). LIMITATIONS: Generalizability is limited to people with a reduction in knee pain. CONCLUSIONS: Reductions in knee pain are not always accompanied by improvements in walking speed. Health providers should consider that the onset of new comorbidity and presence of widespread pain may increase the risk of functional decline despite a reduction in knee pain.